2021
DOI: 10.1155/2021/8850725
|View full text |Cite
|
Sign up to set email alerts
|

Hypervolemic Hyponatremia as a Reversible Cause of Cardiopulmonary Arrest in a Postpartum Patient with Preeclampsia

Abstract: Although the incidence of preeclampsia complicated by hyponatremia is reportedly rare, the effects on the maternal outcome are severe and life-threatening. Here, we describe a case of a patient with preeclampsia who coded postpartum and was discovered to have hypervolemic hyponatremia and subsequently recovered after fluid diuresis and resolution of hyponatremia. While hyponatremia in preeclampsia is rare, it is even more unique for it to lead to cardiopulmonary arrest consequently. Therefore, sodium levels an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A low level of Na (hyponatremia) is the most common electrolyte abnormality that may pose a risk to pregnancy [ 60 ] and contribute to pre-eclampsia, which can result in a shorter pregnancy [ 61 , 62 , 63 ]. Hsu et al [ 64 ] showed that hyponatremia in pre-eclampsia can lead to maternal respiratory and circulatory arrest. This is also confirmed by Powel et al [ 65 ], based on a case report of a twin pregnancy and data from the literature showing that pregnant women should be screened for water–electrolyte balance as part of a risk assessment for pre-eclampsia, as elevated Na levels can also be a risk factor for this condition [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…A low level of Na (hyponatremia) is the most common electrolyte abnormality that may pose a risk to pregnancy [ 60 ] and contribute to pre-eclampsia, which can result in a shorter pregnancy [ 61 , 62 , 63 ]. Hsu et al [ 64 ] showed that hyponatremia in pre-eclampsia can lead to maternal respiratory and circulatory arrest. This is also confirmed by Powel et al [ 65 ], based on a case report of a twin pregnancy and data from the literature showing that pregnant women should be screened for water–electrolyte balance as part of a risk assessment for pre-eclampsia, as elevated Na levels can also be a risk factor for this condition [ 66 ].…”
Section: Discussionmentioning
confidence: 99%